PERADILAN AGAMA DAN SENGKETA EKONOMI SYARI’AH (Studi Atas Efektifitas UU No 3 Tahun 2006 di Kota Metro) - Mufliha Wijayati (istinbath, 2013)
Since the born of Enactment of law No. 3 2006 and Act No. 50 2009 is a new era of religious couts. These acts was a change of Act No. 7 1989 of Religious Courts. The main changes of this law is the existence of absolute territorial expansion of the religious courts to handle economic Syariah dispute. This paper answered how the readiness of religious court Class IB Kota Metro dealing with islamic finance dispute and identified supporting factors and inhibiting factors related to the readiness of religious courts of Kota Metro to handle absolute competence in Islamic finance dispute. The findings of this research showed that the result of observation and interview to the judge, clerk of the court, jury and enterpreneur analyzed by Friedman theory. The result showed that the religious court Kota Metro has been ready to handle islamic finance dispute at the legal substance and legal structure level. The problem was on law culture of citizen that tend to avoid the curiousity toward law and court. As a result, some islamic finance disputes that happened in BMT, BPRS and Bank Syariah compromised out of the court. The solution of the problems were chosen because of some considerations such as case complexity, economic factor and maintaining good relationship factor.